MANAGEMENT OF JUVENILE RHEUMATOID ARTHRITIS (AMAVATA) THROUGH AYURVEDA: A CASE STUDY - Jitendra Varsakiya*; Singh.N.R; Alisha (AYUSHDHARA, 2019)
Juvenile Rheumatoid Arthritis is an autoimmune, non-infective, inflammatory joint disease of more than 6 weeks’ duration in children less than 16 years of age. It is a subset of arthritis seen in childhood, which may be transient and self-limited or chronic. It is comparable to the disease ‘Amavata’ in Ayurveda. In disease Amavata, Ama dosha is being directed into joints by the vitiated Vata Dosha (Vyana Vata) and affects the Shleshma Dhara Kala (can be correlated as synovial tissue inflammation), resulting in effusion and swelling of joints. Due to this restriction of movement and persistent unendurable pain confined patient to bed with limited working area. Approximately 0.05% of total adult population i.e., 2.5 million adults of India are victims of these ailment. A 19 years old male came to Ch.Brahm Prakash Ayurveda Charak Sansthan, Kayachikitsa special OPD with complaint of Angamarda (body ache), Aruchi (loss of appetite), Alasya (weakness), Sandhi Shoola (joint pain), Sandhisopha (joint swelling) over whole body joint and Morning stiffness in multiple joints etc. Examination, investigations and history leads to diagnosis of Juvenile Rheumatoid Arthritis (Amavata). So, patient was treated with internal and external Ayurvedic drugs, Pathya, Apathya and Yogasananas. The treatment modalities done showed marked improvement in the patient’s signs and symptoms and blood investigations and hence, Treatment through Ayurveda has effective results in the management of Juvenile Rheumatoid Arthritis (Amavata).